Reliability of Corneal, Epithelial, and Stromal Thickness Mapping for a 9-mm Zone Using Spectral-Domain Optical Coherence Tomography - Krause, Daniel; Mohr, Niklas; Shajari, Mehdi; Mayer, Wolfgang J.; Priglinger, Siegfried; Luft, Nikolaus (Klinische Monatsblätter für Augenheilkunde, 2021)
Purpose To evaluate the reliability of spectral-domain optical coherence tomography (SD-OCT; RTVue XR; Optovue, Inc., Fremont, CA, USA) for thickness mapping of the entire cornea (CT), corneal epithelium (ET). and corneal stroma (ST) over a 9-mm zone in healthy eyes. We sought to develop reference values for different age groups and elucidate potential sex- and age-dependent characteristics of corneal sublayer pachymetry maps.Methods Three consecutive SD-OCT scans were obtained in 166 healthy right eyes (mean age = 50 ± 20 years). The thickness maps contain 25 sectors over a 9-mm diameter zone. To test measurement reliability, intraclass correlation coefficients (ICC), coefficients of variation (CoV), and within-subject standard deviations (WSSD) were calculated.Results CT, ET, and ST ICCs ranged from 0.961 to 0.998, 0.896 to 0.945, and 0.955 to 0.998, respectively. CoV values for CT, ET, and ST ranged between 0.3 and 1.5%, 1.6 and 4.2%, and 0.4 and 1.7%, respectively. WSSD ranged from 6 to 41, 4 to 8, and 7 to 46 µm, respectively. A negative correlation was found between age and ET (p < 0.05) but not between age and ST or CT. No gender-related differences in CT, ET, or ST were detected. CoV of CT, ET, and ST measurements showed a positive correlation with age in 28, 64, and 28% of the sectors, respectively.Conclusion SD-OCT is a rapid and noninvasive technique that provides excellent reliability for corneal sublayer thickness measurements over a 9-mm zone. The reliability of the ET measurement seems to be negatively affected by age. Peripheral CT and global ET thin with age.
Keywords: cornea; SD-OCT; reliability; anterior segment OCT